yz - x
5 - (-5) = 10
7 subtracted from the quotient of a number and 2 is a -6
To write "5 subtracted from a quarter of s" as an expression, you can first express a quarter of s as s/4, and then subtract 5 from it. The expression would be s/4 - 5.
5-k
5(y+1)-2y5 x y = 5y5 x 1 = 55y + 5 - 2y5y - 2y = 3y3y + 5
13
0
Call the unknown value of (x - y) d. Then x = y + d; from the problem statement, y + d + 2(y + d) +5 = y + 2y; expanding yields y + d + 2y + 2d + 5 = y + 2y; (y + 2 y) can be subtracted from both sides and terms in d collected to result in 3d + 5 = 0; 3d = -5; d = -5/3.
y subtracted by 6 6 less than y
54 subtracted by 49 = 5
17
Since we have no idea where X or Y are, we cannot answer the question.
y = 6x - 32
3.42
25
It is: 5^6 which means 5 to the power of 6